Nickel-iron-chromium-based high-temperature alloy with high strength and high structure stability and preparation method thereof

By optimizing the composition and heat treatment process of nickel-iron-chromium-based high-temperature alloy, a stable γ′ phase structure was formed, which solved the problem of microstructure structure instability of nickel-iron-chromium-based high-temperature alloy, and achieved high strength and strength at 700-800℃ and High tissue stability, suitable for superheaters and reheaters of ultra-supercritical coal-fired generator sets.

CN119320893APending Publication Date: 2025-01-17CHINA HUANENG GRP CO LTD +2

Patent Information

Application Number
CN202411439717.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The microstructure structure of existing nickel iron-chromium-based high-temperature alloys is unstable, resulting in poor macroscopic mechanical properties, which is difficult to meet the requirements of thermal strength, oxidation and corrosion resistance and welding properties of 700℃ level ultra-supercritical coal-fired power generation technology.

Method used

A nickel iron-chromium-based high-temperature alloy is designed, containing elements of specific proportions such as Fe, Cr, Al, Co, Mo, B, W, etc., and is formed by vacuum smelting, annealing, hot rolling, solid solution and aging treatment to form γ' The austenite structure dominated by phase controls the particle size and grain boundary structure of the γ′ phase to ensure the stability and strength of the alloy at high temperatures.

Benefits of technology

It achieves high strength and high tissue stability for long-term use at 700-800°C, reduces the cost of the alloy, improves the oxidation and corrosion resistance of water vapor oxidation, and enhances the hot and cold processing forming and welding performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005086028830000061
    Figure BDA0005086028830000061
  • Figure BDA0005086028830000071
    Figure BDA0005086028830000071
  • Figure HDA0005086028840000011
    Figure HDA0005086028840000011
Patent Text Reader

Abstract

The invention discloses a nickel-iron-chromium-based high-temperature alloy with high strength and high structure stability and a preparation method of the nickel-iron-chromium-based high-temperature alloy. The nickel-iron-chromium-based high-temperature alloy comprises, by weight, 0.03%-0.10% of C, 15%-25% of Fe, 16%-21% of Cr, 1.0%-2.5% of Ti, 0.5%-2.1% of Al, 1.0%-3.0% of Co, 0.3%-1.0% of Mo, 0.001%-0.01% of B, 0.1%-0.5% of W and the balance Ni. According to the nickel-iron-chromium-based high-temperature alloy disclosed by the invention, a gamma'phase and M23C6 are main strengthening phases; compared with the prior art, the material has the advantages of equivalent processability, low material cost and more excellent high-temperature strength and structure thermal stability, and can be used for manufacturing boiler last-stage superheater / reheater pipelines of ultra-supercritical thermal power generating units with the temperature of 700 DEG C and above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of heat treatment of heat-resistant alloys, and specifically relates to a nickel-iron-chromium-based high-temperature alloy with high strength and high structural stability and a preparation method thereof. Background Art

[0002] High-efficiency and clean high-parameter ultra-supercritical coal-fired power generation technology is one of the main development trends of clean coal-fired power generation technology in the world today. The 700℃ advanced ultra-supercritical (A-USC) coal-fired power generation system under development can have a thermal efficiency of over 50%, and the coal consumption for power supply is less than 240g / kW. However, a series of technical problems need to be solved to reach the steam parameter of 700℃. Among them, the development of heat-resistant alloys for boiler final stage superheater / reheater with high thermal strength, good microstructure stability, resistance to high-temperature flue gas oxidation corrosion and high-temperature steam-water medium corrosion, good weldability and processability, and low price is one of the key technical issues in realizing high-parameter ultra-supercritical coal-fired power generation technology.

[0003] At present, the candidate alloy materials abroad are mainly solid solution strengthened and precipitation strengthened Ni-based and Ni-Co-based high temperature alloys, such as Alloy 263, Inconel 740H and Haynes 282. In terms of endurance strength, these alloys can basically meet the service performance requirements of the last stage superheater / reheater of the 700℃ ultra-supercritical thermal power unit boiler. However, it is worth mentioning that due to the rich content of Co and Mo elements, this type of alloy has poor hot forming, is difficult to make large components required for ultra-supercritical, and is expensive, thus limiting their use. It is well known that adding Fe elements to these alloys can significantly reduce their cost and improve their machinability. Therefore, more and more researchers are trying to add Fe elements to these alloys to study their effects on alloy properties and thermal stability of microstructure. For example, Ge Zhanying et al. studied the effect of Fe on the microstructure of Ni-15wt.%Cr-5.5wt.%Mo-3.85wt.%Al-2.6wt.%Ti type Ni-based high temperature alloy and found that when the Fe content is greater than 5wt.%, σ phase begins to precipitate in the alloy after long-term aging at 850℃. At the same time, they also found that with the increase of Fe content, the volume fraction of γ′ phase particles in the alloy gradually decreases. Wang Changshuai et al. compared the thermal stability of the microstructure of Ni-20wt.%Cr-2.2wt.%Mo-1.2wt.%Nb-0.35wt.%Al-1.24wt.%Ti-0.04wt.%C alloys with Fe content of 20wt.%, 25wt.% and 34wt.% and found that after aging at 750℃ for 5000h, η phase precipitated in all alloys, thereby reducing the macroscopic mechanical properties of the alloy. Summary of the invention

[0004] The purpose of the present invention is to address the problem that the microstructure of existing nickel-iron-chromium-based high-temperature alloy materials is unstable, resulting in poor macroscopic mechanical properties, and to propose a nickel-iron-chromium-based high-temperature alloy with high strength and high structural stability, which has reasonable component design, excellent high-temperature strength and structural stability, good processing performance and mechanical properties, and a preparation method thereof.

[0005] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] A nickel-iron-chromium-based high-temperature alloy with high strength and high organizational stability. The nickel-iron-chromium-based high-temperature alloy comprises, by weight percentage, C: 0.03-0.10%, Fe: 15-25%, Cr: 16-21%, Ti: 1.0-2.5%, Al: 0.5-2.1%, Co: 1.0-3.0%, Mo: 0.3-1.0%, B: 0.001-0.01%, W: 0.1-0.5%, and the balance is Ni.

[0007] Furthermore, the nickel-iron-chromium-based high-temperature alloy includes, by weight percentage, C: 0.04-0.08%, Fe: 17-25%, Cr: 17-21%, Ti: 2.0-2.5%, Al: 1.5-2.1%, Co: 1.0-2.5%, Mo: 0.3-1.0%, B: 0.001-0.008%, W: 0.1-0.5%, and the balance is Ni.

[0008] Furthermore, the sum of the weight percentages of Fe and Cr is ≤ 42%.

[0009] Furthermore, the weight percentage ratio of Al to Ti is greater than or equal to 1.2 and less than or equal to 1.4.

[0010] Furthermore, the alloy also contains inevitable impurities, and the impurity contents are as follows by weight percentage: Si: ≤0.05%, Mn: ≤0.3%, P: ≤0.02%, S: ≤0.01%, N: ≤0.01%, and Nb: ≤0.5%.

[0011] A method for preparing a nickel-iron-chromium-based high-temperature alloy with high strength and high structural stability comprises the following steps:

[0012] The alloy is melted under vacuum and cast into alloy ingots;

[0013] homogenizing and annealing the alloy ingot at 1150-1250° C. above the precipitation temperature of the γ′ phase for 24-48 hours to obtain a master alloy ingot;

[0014] The master alloy ingot is subjected to high temperature rolling;

[0015] The alloy after high-temperature rolling is solution treated, water-cooled to room temperature, and then subjected to a first aging treatment and a second aging treatment. The temperature of the first aging treatment is higher than the temperature of the second aging treatment, so as to obtain a nickel-iron-chromium-based high-temperature alloy with high strength and high structural stability.

[0016] Furthermore, the temperature of high temperature rolling is 950-1150°C.

[0017] Furthermore, during high temperature rolling, the deformation amount of each pass is not less than 15-25%, and the final total deformation amount is not less than 60%.

[0018] Furthermore, the temperature of the solution treatment is 1080-1150° C. and the time is 30-60 min.

[0019] Furthermore, the temperature of the first aging treatment is 980-1020°C, the time is 30-120min, and the second aging treatment is performed after water cooling to room temperature. The temperature of the second aging treatment is 650-850°C, the time is 4-24h, and the second aging treatment is performed after water cooling to room temperature.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The alloy of the present invention has better tensile strength and high-temperature structural stability, and is suitable for making superheaters and reheaters in the boilers of ultra-supercritical coal-fired power generation units at 700°C and above, and can be used for a long time at 700-800°C. Compared with nickel-based high-temperature alloys such as Haynes282, Inconel 740 / Inconel 740H, CCA617, Nimonic 263, etc. in Europe and the United States, the alloy of the present invention not only contains a large amount of iron, but also has low content of precious metal elements such as cobalt, molybdenum, tungsten and tantalum, and has the characteristics of low cost. The nickel-iron-chromium-based high-temperature alloy, after heat exposure at 750°C for 3000h, has an average size of γ′ phase particles less than 97nm, a yield strength greater than 550MPa, and has higher yield strength and tensile strength.

[0022] The functions of various main elements in the alloy of the present invention are:

[0023] Ni: The main element that forms the matrix austenite, expands the austenite area, and ensures the structural stability of the alloy at high temperatures.

[0024] Fe: Adding an appropriate amount of iron to replace nickel in nickel-based alloys can not only reduce the cost of the alloy, but also improve the hot workability of the alloy, and has a solid solution strengthening effect on austenite Ni. However, excessive Fe elements tend to promote the formation of harmful phases σ phase and α-Cr, and also reduce the alloy's oxidation corrosion resistance. Therefore, the Fe content of the alloy is specified to be 17-25%.

[0025] Co: Adding an appropriate amount of Co to nickel-based alloys can reduce their stacking fault energy and improve their high-temperature strength; at the same time, adding Co to the alloy can also inhibit the precipitation of harmful topological close-packed phase (TCP). However, excessive Co will significantly increase the cost of the alloy and reduce the tensile rupture plasticity of the alloy.

[0026] Cr and Al: The main function of Cr is to improve the alloy's anti-oxidation, anti-water vapor oxidation and corrosion resistance, especially sulfuric acid corrosion resistance. At high temperatures, it reacts with oxidation to form complete and dense Cr2O3 and Al2O3 protective films. At high temperatures of 650-800°C, in order to ensure that the alloy of the present invention resists 700°C ultra-supercritical water vapor oxidation corrosion, the Cr content must be above 14% and the Al content must be above 1.5%. The higher the Cr content in the alloy, the better the above-mentioned anti-oxidation properties. However, too high a Cr content will promote the precipitation of TCP phase and the formation of α-Cr. Therefore, the Cr content of the alloy of the present invention should be controlled at 15-21%, and the preferred content is 17-21%. And the Fe+Cr weight percentage is ≤42%.

[0027] Al and Ti: Elements that form the main strengthening phase γ′-Ni3(Al,Ti) in the alloy. In addition, Al can improve the alloy's ability to resist oxidation, and Ti has the effect of resisting hot corrosion and sulfidation corrosion. However, when the Ti content is too high, especially when the Ti / Al ratio is too high, it will induce the precipitation of η-Ni3Ti phase, increase the mismatch between γ / γ′ phases, increase the coarsening rate of γ′ phase, and reduce the strength of the alloy.

[0028] Mo, W and Ta: important solid solution strengthening elements, which greatly promote the high temperature strength and durability of the alloy. However, too high Mo content is prone to pitting, and too high W and Ta content is prone to segregation during alloy smelting, reducing the hot workability of the alloy. Therefore, the Mo content should be controlled to be less than 2%, preferably 0.5-1.0%; the W content should be controlled to be less than 2%, preferably less than 1.0%; the Ta content should be controlled to be less than 1%.

[0029] Si: An important deoxidizing element. Adding it in appropriate amounts can also improve the alloy's anti-oxidation properties. However, too high a Si content will reduce the alloy's thermal processing and welding properties. Therefore, the Si content should be controlled to be less than 0.5%.

[0030] C, B, Zr: Adding trace amounts of C, B and Zr grain boundary segregation elements can change the interatomic bonds and states of the grain boundaries, increase the bonding mechanism of the grain boundaries, strengthen and purify the grain boundaries, and thus improve the strength of the alloy. Elements such as Ti, W, Mo and Cr in C and B element alloys are prone to form carbides and borides. The carbides and borides that precipitate at the grain boundaries can play a pinning role on the grain boundaries, thereby improving the durability of the alloy. However, if the C and B content is too high or the heat treatment is not appropriate, too much carbide will make the grain boundaries brittle and significantly reduce the creep plasticity.

[0031] The performance of the alloy of the present invention depends not only on the alloy composition, but also on the microstructure of the alloy. The microstructure of the alloy is determined by the smelting, thermal deformation and heat treatment process of the alloy. The preparation method of the high-strength and high-microstructure stability nickel-iron-chromium-based high-temperature alloy of the present invention can be smelted in a vacuum induction furnace, and the subsequent forming and deformation are generally performed by casting and thermal deformation (hot rolling or hot extrusion), and no special process is required for production. The nickel-iron-chromium-based high-temperature alloy, after solution and aging treatment, has a high-strength and high-microstructure stability nickel-iron-chromium-based high-temperature alloy that is a disordered face-centered cubic austenite, the main strengthening phase is the γ′ phase, and there are MC-type carbides and M at the grain boundaries and twin boundaries. 23 C6 type carbide; when the grain size is 89-127 μm, the γ′ phase size is 20-30 nm, the yield strength at 750° C. is greater than 640 MPa, the tensile strength is greater than 690 MPa, and the elongation is greater than 6.5%. The nickel-iron-chromium-based high-temperature alloy prepared by the present invention has no discontinuous precipitation phase formed at the grain boundary, and after heat exposure at 700° C. and 750° C. for 10,000 hours, the average size of the γ′ phase particles is less than 75 nm and 145 nm, respectively, and no α-Cr phase and topological close-packed phase are precipitated in the alloy.

[0032] Furthermore, the alloy of the present invention can be cooled by water cooling after solid solution and aging treatment, thereby improving the alloy's cold and hot processing formability and welding performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The metallographic structure of the alloy of Example 1 of the present invention; in the figure: (a) is a low magnification; (b) is a high magnification;

[0034] Figure 2 Metallographic structure of alloy of comparative example 1; in the figure: (a) is low magnification; (b) is high magnification;

[0035] Figure 3 The metallographic structure of the alloy of Example 1 of the present invention after long-term aging at 700°C / 10000h, in which: (a) is a low magnification; (b) is a high magnification;

[0036] Figure 4 The metallographic structure of the alloy of Example 1 of the present invention after long-term aging at 750°C / 10000h, in which: (a) is a low magnification; (b) is a high magnification;

[0037] Figure 5 The metallographic structure of the alloy of comparative example 1 of the present invention after long-term aging at 700°C / 10000h, in which: (a) is a low magnification; (b) is a high magnification;

[0038] Figure 6This is the metallographic structure of the alloy of comparative example 1 of the present invention after long-term aging at 750°C / 10000h, in which: (a) is a low magnification; (b) is a high magnification. DETAILED DESCRIPTION

[0039] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.

[0040] The nickel-iron-chromium-based high-temperature alloy obtained by the present invention has the characteristics of high strength and high organizational stability at 700-800°C, the matrix of which is austenite with a face-centered cubic structure, the main strengthening phase is γ′-Ni3(Al,Ti), and there is M at the grain boundary and twin boundary. 23 C6, when the grain size range is 89-127μm, the yield strength at 750℃ is greater than 640MPa, the tensile strength is greater than 690MPa, and the elongation is greater than 6.5%.

[0041] Example 1

[0042] 1. Alloy composition

[0043] Table 1 shows the chemical composition of Example 1 of the present invention. In order to compare with the relatively mature similar applications No.: 201210513438.0, entitled: A high-strength and corrosion-resistant nickel-iron-chromium-based high-temperature alloy and a nickel-iron-chromium-based high-temperature alloy prepared by its preparation method (Comparative Example 1) and No.: 201310468308.4, entitled: A hot corrosion-resistant nickel-iron-based deformed high-temperature alloy and a preparation method and application thereof, and No.: 201911296733.3, entitled: A high-strength and high-toughness anti-oxidation iron-nickel-based high-temperature alloy and an iron-nickel-based high-temperature alloy prepared by its preparation method (Comparative Example 3), the compositions of these three alloys are also listed in the table.

[0044] Table 1 Chemical composition of Example 1 of the present invention and Comparative Examples 1-3 (wt %, balance Ni)

[0045]

[0046]

[0047] 2. Melting and thermal deformation of alloy

[0048] In terms of weight percentage, C: 0.05%, Fe: 19%, Cr: 19%, Ti: 2.5%, Al: 1.8%, Co: 2.0%, Mo: 0.6%, B: 0.002%, W: 0.2% and the balance Ni are added into a vacuum induction furnace for melting and cast into alloy ingots.

[0049] The alloy ingot is homogenized and annealed at 1200°C for 24-48h; then the master alloy ingot after homogenization and annealing is subjected to multiple hot deformations (hot forging or hot rolling) at 1120°C, with each deformation amount not less than 20%, and the final total deformation amount not less than 60%. The alloy of Example 1 has good hot working properties, and no defects such as cracks appear during the hot working process.

[0050] 3. Heat treatment of alloy

[0051] The hot-deformed alloy was solution treated at 1140°C for 40 minutes, water-cooled to room temperature, then aged at 980-1020°C for 90 minutes, water-cooled to room temperature, and finally aged at 780°C for 20 hours and water-cooled to obtain a nickel-iron-chromium based high-temperature alloy with high strength and high organizational stability.

[0052] 4. Initial structural characteristics of the alloy

[0053] The grain size of the alloy ranges from 89 to 127 μm, and its typical structural characteristics are Figure 1 As shown in (a) and (b). There are a small amount of MC carbides in the grain, and discontinuous M 23 C6 type carbide. The main strengthening phase in the crystal is γ′ phase, and the size of γ′ phase is 20-30nm.

[0054] 5. Tensile strength of alloy

[0055] The tensile properties of the alloy of Example 1 at 750°C are shown in Table 2. For comparison, the table also lists the tensile properties of the alloys of Comparative Examples 1 and 2 at 750°C. It can be seen from Table 2 that at 750°C, the yield strength and tensile strength of the alloy of Example 1 are greater than those of the alloys of Comparative Example 1, Comparative Example 2, and Comparative Example 3.

[0056] Table 2 Tensile strength of the alloy of Example 1 and the alloys of Comparative Examples 1 and 2 at 750°C

[0057] alloy Tensile strength / MPa Yield strength / MPa Example 1 729 687 Comparative Example 1 697 638 Comparative Example 2 650 465 Comparative Example 3 599 592

[0058] 6. Thermal stability of alloy microstructure

[0059] The alloy of comparative example 1 was prepared by the same preparation method as that of example 1. The typical microstructure of the alloy is as follows: Figure 2 As shown. Figure 2As can be seen in (a) and (b), the grain size of the alloy ranges from 89 to 127 μm. There are a small amount of MC carbides in the grains, and discontinuous M at the grain boundaries and twin boundaries. 23 C6 carbide. The main strengthening phase in the crystal is γ′ phase, and the size of γ′ phase is 20-30nm. Figure 1 and Figure 2 It can be found that there are discontinuous precipitated phases at the grain boundaries of the alloy of Comparative Example 1, while these precipitated phases are not found at the grain boundaries of the alloy of Example 1. These precipitated phases usually deteriorate the mechanical properties of the alloy.

[0060] On the other hand, the alloy of Example 1, the alloy of Comparative Example 1 and the alloy of Comparative Example 2 were aged at 700°C and 750°C for 10000 h, respectively. Figure 3 (a) and (b) and Figure 4 (a) and (b), while the microstructure of the alloy in comparative example 1 after aging for 10000h is as follows Figure 5 (a) and (b) and Figure 6 (a) and (b). After aging at 700℃ and 750℃ for 10000h, the γ′ phase size of the alloy of Example 1 was 72nm and 137nm, respectively. After aging at 700℃ and 750℃ for 10000h, the γ′ phase size of the alloy of Comparative Example 1 was 72nm and 140nm, respectively. After aging at 700℃ and 750℃ for 10000h, the γ′ phase size of the alloy of Comparative Example 2 was 113nm and 178nm, respectively. This shows that the thermal stability of the main strengthening phase γ′ phase of the alloy of Example 1 is equivalent to that of the alloy of Comparative Example 1, but better than the thermal stability of the γ′ phase in the alloy of Comparative Example 2. At the same time, after aging at 700℃ and 750℃ for 10000h, no TCP phase and needle-shaped α-Cr precipitation were found in the alloy of Example 1 and the alloy of Comparative Example 2, while a small amount of needle-shaped α-Cr precipitation was found in the alloy of Comparative Example 1. The precipitation of these phases usually deteriorates the high temperature rupture strength of the alloy.

[0061] The nickel-iron-chromium-based high-temperature alloy of the present invention has higher high-temperature strength and high structural stability than the alloys of comparative examples 1 to 3. The nickel-iron-chromium-based high-temperature alloy of the present invention is suitable for making superheaters and reheaters in 700°C ultra-supercritical coal-fired power generation units and can be used for a long time at 700-800°C.

[0062] The chemical composition of the alloys described in Examples 2-9 of the present invention is shown in Table 3.

[0063] Table 3 Chemical composition of the alloys described in Examples 2-9

[0064] Example 2 3 4 5 6 7 8 9 Fe 25 24 18 20 21 19 17 22 Cr 17 18 21 19 19 20 20 18 Mo 0.4 0.3 0.6 0.5 0.4 0.9 1.0 0.4 W 0.5 0.1 0.2 0.3 0.4 0.2 0.1 0.3 Co 2.5 2.5 2.0 1.5 2.0 2.0 1.0 2.5 Al 2.1 2.1 1.5 2.0 1.7 1.6 1.8 1.9 Ti 2.4 2.5 2.1 2.2 2.3 2.2 2.0 2.4 C 0.08 0.06 0.05 0.07 0.05 0.07 0.04 0.06 B 0.001 0.008 0.005 0.003 0.005 0.004 0.006 0.002 Si 0.03 0.02 0.05 0.03 0.05 0.02 0.05 0.01 Mn ≤0.3% ≤0.3% ≤0.3% ≤0.3% ≤0.3% ≤0.3% ≤0.3% ≤0.3% Nb ≤0.5% ≤0.5% ≤0.5% ≤0.5% ≤0.5% ≤0.5% ≤0.5% ≤0.5% P ≤0.01 ≤0.01 ≤0.01 ≤0.01 ≤0.01 ≤0.01 ≤0.01 ≤0.01 Ni margin margin margin margin margin margin margin margin

[0065] Example 2

[0066] A method for preparing a nickel-iron-chromium-based high-temperature alloy with high strength and high structural stability comprises the following steps:

[0067] Step 1, melting the alloy under vacuum and casting it into an alloy ingot;

[0068] Step 2, homogenizing and annealing the master alloy ingot smelted in step 1 at 1150° C., which is above the precipitation temperature of the γ′ phase, for 48 hours;

[0069] Step 3: high temperature rolling the master alloy ingot after homogenization annealing treatment in step 2 at 1000° C., with the deformation amount of each pass not less than 20% and the final total deformation amount not less than 60%;

[0070] Step 4: The hot-deformed alloy is solution treated at 1080°C for 60 minutes, water-cooled to room temperature, then aged at 990°C for 110 minutes, water-cooled to room temperature, and finally aged at 850°C for 4 hours and water-cooled to obtain a nickel-iron-chromium-based high-temperature alloy with high strength and high organizational stability.

[0071] Example 3

[0072] A method for preparing a nickel-iron-chromium-based high-temperature alloy with high strength and high structural stability comprises the following steps:

[0073] Step 1, melting the alloy under vacuum and casting it into an alloy ingot;

[0074] Step 2, homogenizing and annealing the master alloy ingot smelted in step 1 at 1250° C., which is above the precipitation temperature of the γ′ phase, for 24 hours;

[0075] Step 3: high temperature rolling the master alloy ingot after homogenization annealing treatment in step 2 at 950° C., with the deformation amount of each pass not less than 15% and the final total deformation amount not less than 60%;

[0076] Step 4: The hot-deformed alloy is solution treated at 1100°C for 40 minutes, water-cooled to room temperature, then aged at 1000°C for 60 minutes, water-cooled to room temperature, and finally aged at 690°C for 24 hours and water-cooled to obtain a nickel-iron-chromium-based high-temperature alloy with high strength and high organizational stability.

[0077] Example 4

[0078] A method for preparing a nickel-iron-chromium-based high-temperature alloy with high strength and high structural stability comprises the following steps:

[0079] Step 1, melting the alloy under vacuum and casting it into an alloy ingot;

[0080] Step 2, homogenizing and annealing the master alloy ingot smelted in step 1 at 1150° C., which is above the precipitation temperature of the γ′ phase, for 48 hours;

[0081] Step 3: high temperature rolling the master alloy ingot after homogenization annealing treatment in step 2 at 1150° C., with the deformation amount of each pass not less than 25% and the final total deformation amount not less than 60%;

[0082] Step 4: The hot-deformed alloy is solution treated at 1150°C for 30 minutes, water-cooled to room temperature, then aged at 980°C for 120 minutes, water-cooled to room temperature, and finally aged at 700°C for 22 hours and water-cooled to obtain a nickel-iron-chromium-based high-temperature alloy with high strength and high organizational stability.

[0083] Example 5

[0084] A method for preparing a nickel-iron-chromium-based high-temperature alloy with high strength and high structural stability comprises the following steps:

[0085] Step 1, melting the alloy under vacuum and casting it into an alloy ingot;

[0086] Step 2, homogenizing and annealing the master alloy ingot smelted in step 1 at 1100° C., which is above the precipitation temperature of the γ′ phase, for 30 hours;

[0087] Step 3: The master alloy ingot after homogenization annealing treatment in step 2 is subjected to high temperature rolling at 1100° C., with the deformation amount of each pass not less than 25% and the final total deformation amount not less than 60%;

[0088] Step 4: The hot-deformed alloy is solution treated at 1120°C for 40 minutes, water-cooled to room temperature, then aged at 1020°C for 30 minutes, water-cooled to room temperature, and finally aged at 800°C for 8 hours and water-cooled to obtain a nickel-iron-chromium-based high-temperature alloy with high strength and high organizational stability.

[0089] The preparation methods of Examples 6 to 9 are the same as those of Example 2.

[0090] Since the composition, organizational structure and performance of high-temperature materials are closely related, the present invention can optimize the composition of the alloy to maintain the high strength and high organizational stability of the alloy while having good toughness and steam oxidation resistance.

[0091] Compared with the nickel-iron-chromium-based high-temperature alloy prepared by the application number: 201210513438.0, entitled: A high-strength and corrosion-resistant nickel-iron-chromium-based high-temperature alloy and its preparation method, the alloy of the present invention has better tensile strength and high-temperature structural stability, is suitable for making superheaters and reheaters in ultra-supercritical coal-fired power generation unit boilers of 700°C and above, and can be used for a long time at 700-800°C.

[0092] Compared with the nickel-iron-chromium-based high-temperature alloy prepared by the application number: 201210513438.0, entitled: A high-strength and corrosion-resistant nickel-iron-chromium-based high-temperature alloy and its preparation method, the alloy of the present invention can be cooled by water quenching after solid solution and aging treatment, thereby improving the alloy's cold and hot processing formability and welding performance.

[0093] Compared with the nickel-iron-chromium-based high-temperature alloy prepared by the application number: 201310468308.4, entitled: A hot-corrosion-resistant nickel-iron-based deformed high-temperature alloy and its preparation method and application thereof, and the iron-nickel-based high-temperature alloy prepared by the application number: 201911296733.3, entitled: A high-strength, high-toughness, oxidation-resistant iron-nickel-based high-temperature alloy and its preparation method, the alloy of the present invention has higher yield strength and tensile strength.

[0094] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.

[0095] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

Claims

1. A nickel-iron-chromium-based high-temperature alloy with high strength and high structural stability, characterized in that: Calculated by weight percentage, the nickel-iron-chromium-based high-temperature alloy includes C: 0.03-0.10%, Fe: 15-25%, Cr: 16-21%, Ti: 1.0-2.5%, Al: 0.5-2.1%, Co: 1.0-3.0%, Mo: 0.3-1.0%, B: 0.001-0.01%, W: 0.1-0.5%, and the balance is Ni.

2. The nickel-iron-chromium-based high-temperature alloy with high strength and high structural stability according to claim 1, characterized in that: Calculated by weight percentage, the nickel-iron-chromium based high temperature alloy includes C: 0.04-0.08%, Fe: 17-25%, Cr: 17-21%, Ti: 2.0-2.5%, Al: 1.5-2.1%, Co: 1.0-2.5%, Mo: 0.3-1.0%, B: 0.001-0.008%, W: 0.1-0.5%, and the balance is Ni.

3. The nickel-iron-chromium-based high-temperature alloy with high strength and high structural stability according to claim 1, characterized in that: The sum of the weight percentages of Fe and Cr is ≤42%.

4. The nickel-iron-chromium-based high-temperature alloy with high strength and high structural stability according to claim 1, characterized in that: The weight percentage ratio of Al to Ti is greater than or equal to 1.2 and less than or equal to 1.

4.

5. The nickel-iron-chromium-based high-temperature alloy with high strength and high structural stability according to claim 1, characterized in that: The alloy also contains inevitable impurities, and the impurity contents are as follows by weight: Si: ≤0.05%, Mn: ≤0.3%, P: ≤0.02%, S: ≤0.01%, N: ≤0.01%, Nb: ≤0.5%.

6. A method for preparing a nickel-iron-chromium-based high-temperature alloy with high strength and high structural stability, characterized in that: The steps include: Melting the alloy according to any one of claims 1 to 5 under vacuum and casting into an alloy ingot; homogenizing and annealing the alloy ingot at 1150-1250° C. above the precipitation temperature of the γ′ phase for 24-48 hours to obtain a master alloy ingot; The master alloy ingot is subjected to high temperature rolling; The alloy after high-temperature rolling is solution treated, water-cooled to room temperature, and then subjected to a first aging treatment and a second aging treatment. The temperature of the first aging treatment is higher than the temperature of the second aging treatment, so as to obtain a nickel-iron-chromium-based high-temperature alloy with high strength and high structural stability.

7. The method for preparing the nickel-iron-chromium-based high-temperature alloy with high strength and high structural stability according to claim 6, characterized in that: The temperature of high temperature rolling is 950-1150℃.

8. The method for preparing the nickel-iron-chromium-based high-temperature alloy with high strength and high structural stability according to claim 6, characterized in that: During high temperature rolling, the deformation of each pass is not less than 15-25%, and the final total deformation is not less than 60%.

9. The method for preparing the nickel-iron-chromium-based high-temperature alloy with high strength and high structural stability according to claim 6, characterized in that: The temperature of the solution treatment is 1080-1150°C and the time is 30-60 minutes.

10. The method for preparing the nickel-iron-chromium-based high-temperature alloy with high strength and high structural stability according to claim 6, characterized in that: The temperature of the first aging treatment is 980-1020°C, the time is 30-120min, and the second aging treatment is carried out after water cooling to room temperature. The temperature of the second aging treatment is 650-850°C, the time is 4-24h, and the second aging treatment is water cooled to room temperature.

Citation Information

Patent Citations

  • High-strength and corrosion-resistant nickel-iron-chromium-based high-temperature alloy and preparation method for same

    CN102994809B

  • Thermal corrosion-resistant nickel-iron based high-temperature deformation alloy and preparation method and applications thereof

    CN104513917A

  • High-strength high-toughness antioxidant iron-nickel-based high-temperature alloy and preparation method thereof

    CN110952016A

Cited By

  • Ternary nickel-based titanium-niobium alloy resistant to high temperature of 2500 DEG C and preparation method thereof

    CN122168960A